The Changing Incidence and Severity of Poverty Spells among Female-Headed Families - Card, David; Blank, Rebecca M (American Economic Review, 2008)
The Changing Incidence and Severity of Poverty Spells among Female-Headed Families by David Card and Rebecca M. Blank. Published in volume 98, issue 2, pages 387-91 of American Economic Review, May 2008